Rafael Alberti en su exilio argentino - Prenz, Ana Cecilia (Ars et humanitas, 2017)
The present article takes as a starting point an expression of Mujica Láinez, "our heterogeneous contributions" mentioned in the literary guide to Buenos Aires written by Álvaro Abós, in order to enter into the literary world of Rafael Alberti. In particular, the autobiographical book La arboleda perdida (The Lost Grove), considered in its double dimension, is either a book of memories or a novel. The elements and objects associated between Spanish and Argentine life among the various groves, located superficially at the sites where the poet lived, are transmuted, profoundly, into a single grove that becomes a symbolic motif in his writing
Keywords: Alberti, Rafael; avtobiografije; izgnanstvo; literarne študije; španska književnost